System of crop intensification integrated management of crops for improving sustainability and resilience to climate change - Gupta, Gaurendra; Dhar, Shiva; Kumar, Amit; Kamboj, Navish Kumar; Kumar, Vikram (Indian Farming, 2018)
A high-chemical and highirrigation based agriculture while giving short-term returns, damages soil-health, eco-balance and agricultural sustainability in the long run. Thus, there is an urgent need to build soil-health systematically and to maintain it. It is important to increase the productivity and resilience of land resources. System of crop intensification is one of those practices which aim to improve the productivity, sustainability, food security and resilience to climate change by altering the traditional practices of crop, soil, water and nutrient management. Principles of system of crop intensification can be applied in various crops such as rice, wheat, sugarcane, mustard. System of crop intensification practices enable the crop to grow and develop potentially which provides enhanced production in sustainable and ecofriendly manner. Therefore, classical crop cultivation practices needs to overhaul by adopting system of crop intensification for more profitable and sustainable agriculture.